Low Noise Amplifier at 60 GHz Using Low Loss On-Chip Inductors - Karthigha Balamurugan; M. Nirmala Devi; M. Jayakumar (Journal of Electrical and Computer Engineering)
This paper proposes the technique of using low loss on-chip inductors in the design of low noise amplifier (LNA) that offers high gain and lower noise figure. Upon the substrate of octagonal spiral inductors, a surface of patterned ground shield is inserted that significantly reduces the substrate loss. This effect limits the penetration of electric filed into the substrate, thereby improving the inductor’s Quality (Q) factor and decouples the substrate parasitic that results with smaller series resistance. These effects result with improved gain and noise figure of LNA at 60 GHz when the designed inductors are included in it to serve as gate, source, and load inductances. The proposed work uses an inductively degenerated 3-stage common-source LNA in a 65-nm CMOS process. Simulation results show that the LNA using custom designed inductors achieves the peak gain of 17.02 dB at 56 GHz with a noise figure of 5 dB at 60 GHz for the power consumption of 10 mW. The figure-of-merit (FOM) is 14.56 which is 0.8 times more than the LNA design using off-chip inductors. A complete LNA layout using custom designed inductor footprints has been presented and analyzed.